Education policy : globalization, citizenship and democracy - Olssen, Mark (Sage, 2004)
Education Policy provides an international perspective on education policy, and of the role and function of education in the global economy. It covers the major topics of central significance in education and the sociology of education. At the same time it maintains a unique position in respect to globalization, education and the nation state.